2022
DOI: 10.1177/17470161221094929
|View full text |Cite
|
Sign up to set email alerts
|

The intervening effect of the What Being the Parent of a New Baby is Like-Revised questionnaire on maternal affect

Abstract: The ‘What Being the Parent of a New Baby is Like-Revised’ (WPL-R) is an instrument designed to measure adaptation to parenthood. In the process of pilot testing and validating the WPL-R in a postpartum Dutch population, we became aware of the potentially sensitive nature of the measure. Despite the ethics committee waiving the invasive nature of the measure, we conducted a survey to explore its possible effect on women’s thoughts and emotions by using the Positive And Negative Affect Schedule (PANAS) to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Interestingly, participants in the present study also endorsed high levels of PANAS-PA (M = 41). By comparison, Spanish university students reported lower PA before the pandemic (M = 33) and in March 2020 (M = 25;Mayor-Silva et al, 2022), adults reported lower PA in October 2020 (M = 34; Orfei et al, 2022), and 152 Dutch parents of new babies reported lower PA in April 2020 (M = 35;van Beeck et al, 2022). It is possible that parents with relatively high PA may have been particularly drawn to participate in this study, as it is a part of a larger randomized controlled trial examining app-based interventions rooted in positive psychology (i.e., gratitude and mindfulness).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, participants in the present study also endorsed high levels of PANAS-PA (M = 41). By comparison, Spanish university students reported lower PA before the pandemic (M = 33) and in March 2020 (M = 25;Mayor-Silva et al, 2022), adults reported lower PA in October 2020 (M = 34; Orfei et al, 2022), and 152 Dutch parents of new babies reported lower PA in April 2020 (M = 35;van Beeck et al, 2022). It is possible that parents with relatively high PA may have been particularly drawn to participate in this study, as it is a part of a larger randomized controlled trial examining app-based interventions rooted in positive psychology (i.e., gratitude and mindfulness).…”
Section: Discussionmentioning
confidence: 92%
“…Various conditions emerged for transitional support to be an integral part of the midwife's scope of practice. The findings suggest that this can only occur when the midwife can base support on both professional knowledge about the transitional process (education) and the experiential knowledge of the woman [5, 49]. The midwife also has to regard maternal emotional health as equally important as physical health [8, 53–55].…”
Section: Discussionmentioning
confidence: 99%
“…Becoming a mother involves attaining the maternal identity and role [1]. The overall expectation is that, at the end of the transition process, mothers have achieved a certain balance in their life and are able to navigate the new sense of self and the changes in social and intimate relationships [4][5][6]. Although many women advance through the transition process without major difficulties and adapt well to their new role and identity, feelings of insecurity, stress, anxiety, fears, and worries are reported during this period of transition [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations